Why do the Students Rely on an English Dictionary to Speak English? - Yestanius Waruwu (Journal of English for Specific Purposes in Indonesia, 2024)
English communication is very important in this era. Students are expected to have proficient English skills. However, in reality, students often use English dictionaries when talking to others. A dictionary is a collection of words that functions as a reference that provides translations of words, meanings, and how to read words. Therefore, this research provide an overview of students who often rely on dictionaries when speaking English with other people. The purpose of this research is to see the presentations of students who rely on dictionaries when talking to other people. That way, it will be easier to conclude whether using a dictionary helps students or makes students dependent and ultimately unable to speak English fluently. The research method used is quantitative. Data were collected by using a survey method. The survey method aims to collect data as appropriate by giving questionnaires to the sample to be studied. To maximize the data collected, the survey that the researchers distributed used a Likert Item scale. The participants consisted of 85 of 5th semester students of the English Education Study Program at The University of Nias. The research results show that students still rely on using dictionaries when speaking English.  The ongoing reliance on dictionaries indeed carries a detrimental effect; hence, it is recommended that dictionaries be employed only when necessary.